Impact of the Joint Commission Pneumonia Core Measure on Antibiotic Use and Selection for Community-Acquired Pneumonia in the Emergency Room. Issue 2 (February 2016) - Bulloch, Marilyn N.; Tapley, Natalie G.; Sivaraman, Boopathy; Parton, Jason M.
Background: Prior to 2012, The Joint Commission (TJC) pneumonia core measure (PN-5) required antibiotic administration for suspected community-acquired pneumonia (CAP) within 6 hours of arrival to the emergency room (ER). In 2012, TJC issued PN-6 requiring antibiotic administration within 24 hours of presentation. Though PN-6 was anticipated to reduce overuse and inappropriate antibiotic use and improve appropriate antibiotic selection, the impact of PN-5 and PN-6 on optimizing care for CAP in the ER remains unknown. Objective: To investigate the impact of TJC pneumonia core measures on antibiotic use in the ER for suspected CAP. Methods: In this single-center study, medical records of patients 18 years old and older diagnosed with CAP in the ER during 2011 (PN-5) and 2012 (PN-6) and admitted for 1 day or longer were reviewed. Exclusion criteria included criteria for health care–associated pneumonia. Comparisons between groups were performed using descriptive statistics and contingency table analysis with chi-square or Fisher exact tests for categorical variables and t tests for continuous variables. Statistical analyses were performed using Microsoft Excel 2010 and SAS version 9.4. Results: Antibiotic use was comparable between PN-5 and PN-6. Approximately half of patients in each group received an appropriate empiric CAP regimen (52% vs 54%; P = .807). Among inappropriate regimens, the most common reason was use of a beta-lactam alone (69% vs 83%; P = .26). More patients had an ultimate diagnosis of CAP with PN-6 (78% vs 86%; P = .3). Conclusion: Changes in pneumonia core measure requirements did not have a significant impact on appropriate antibiotic use in the ER.